Acceptance and adoption of biofortified crops in low- and middle-income countries - Talsma, Elise F.; Melse-Boonstra, Alida; Brouwer, Inge D. (International Center for Tropical Agriculture, 2016)
Biofortification of staple crops through conventional plant breeding, genetic engineering or agronomic approaches, is a promising strategy for increasing dietary nutrient density to improve human health. Successful implementation depends, amongst others, on willingness of consumers and farmers to accept the newly bred crop varieties.